IDENTIFICATION OF RAINFALL DISTRIBUTION IN WEST SUMATERA AND ASSESSMENT OF ITS PARAMETERS USING BAYES METHOD - Yanuar, Ferra; Sari, Putri Trisna; Asdi, Yudiantri (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2020)
One distribution of rainfall data is a lognormal distribution with location parameters Â and scale parameters . This study aims to estimate the mean and variance of rainfall data in several selected cities and regencies in West Sumatra. Parameter estimation is estimated by using maximum likelihood estimation (direct method) and Bayes method. This study resulted that the Bayes method produces a better predictive value with a smaller variance value than with direct estimation. It was concluded that the estimation by the Bayes method was a better estimator method than the direct estimation.